BUILDING STUDENT’S MOTIVATION THROUGH “FOCUS GROUPDISCUSSION(FGD)” AS A LEARNING STRATEGYTO ENHANCE SPEAKING COMPETENCEAT SMA NEGERI 7 YOGYAKARTA - Herawati, Reni (Jurnal Ilmiah Guru Caraka Olah Pikir Edukatif, 2013)
This paper outlines the results of a survey which was carried out, to identifystudents’ motivation and attitudes towards English learning especially speaking.Teaching English, especially speaking at Class XI IPA 1, SMA N 7 Yogyakarta,is very challenging. However, the writer as the teacher found some problems inlearning process at the early school year. To have an effective learning process shehad to manage the class into active and motivated classes, hence, a daunting taskin terms of designing an activity that would serve to develop the students’ speakingskills emerged. The atmosphere that was not conducive in the classes consisting ofstudents derived from different previous classes. They were commonly unable toget along well and tend to be silent and passive. This had led the writer to makean effort to find an effective learning strategy to be implemented in her speakingclass. The researcher performed a research entitled “Building Student’s Motivationthrough Focus Group Discussion (FGD) as a Learning Strategy to Enhance Students’Speaking Competence at SMA Negeri 7 Yogyakarta”. This research was aiming atdescribing the effectiveness of FGD as the learning strategy to enhance the students’motivation; describing how it could enhance speaking capability among the studentsof SMA N 7 Yogyakarta. Some valuable findings were proven. There was a significantimprovement in the student’s motivation. They were creating conducive class.They were getting better gradually in developing and organizing idea. All studentswere supposed to get opportunity to be involved in active class participation; asa result, the class lived up. This learning strategy could guide students to becomemotivated, autonomous, and confident students. To top all, “FGD” was proven tobe an effective technique to solve the problems of lack motivation at Class XI IPA1, SMAN 7 Yogyakarta and to enhance the students’ competence of speaking.